PENENTUAN LOKASI POTENSIAL UNTUK PENGEMBANGAN TERMINAL TIPE B SEBAGAI ALTERNATIF PENGGANTI TERMINAL CIBINONG DI WILAYAH ZONA CIBINONG RAYA KABUPATEN BOGOR - Dita Anggraeni; Sucahyanto Sucahyanto; Ode Sofyan Hardi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2016)
ABSTRACT This research aims to map the location of a potential designed as the location to develop B type terminal as an alternative of Cibinong terminal in Cibinong Zone Raya Bogor Regency. This research was conducted in six districts in Cibinong Raya zone region. The districts are Cibinong, Citeureup, Sukaraja, Babakan Madang, Bojong Gede, and Tajur Halang. The researcher used descriptive method as the research method. The technique of data analysis refers to the suitability matrix that has been made under the term parameters of type-B terminal development. The parameters were given the scoring and then processed further by the geographical information system software. After that, the processed results were classified into some classes based on the suitability level of each parameter. The three classifications are the result of the total scores divided into three classifications. For Potential 1 (P1) with a range 14-20, Potential 2 (P2) with a range 713 and Potential 3 (P3) with a range 0-6. The result showed that based on data processing geographical information system in these included in classifying according 1 ( potential 1 ) spread right and left sides jakarta-bogor roads , major oking jayaatmaja cibinong , sukahati-karadenan and the brave believe. Classifying according to 2 ( potential 2 ) spread in roads major oking jayaatmaja citeureup, the kranggan – gunung putri and highways jagorawi. To determine the locations is 3 potential zone with the highest states to be terminals,this zone is Cibinong Zone , Karadenan Zone and Sukahati Zone. Of the three the zone,Cibinong Zone the most suitable to be locations terminal development. Keywords: Potential, Location, Terminal